Analisis Pengelolaan Keuangan UMKM di Sektor Kuliner dalam Meningkatkan Keberlanjutan Usaha - Nisrina, Ulfah Laila (Jurnal Ilmiah Manajemen & Kewirausahaan, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia’s economic development, especially in the culinary sector, which is experiencing significant growth in Parepare City. However, weak financial management remains a major challenge to business sustainability. This study aims to analyze financial management practices among culinary MSMEs in Parepare and their impact on business sustainability. This study uses a descriptive qualitative approach with data collection techniques in the form of interviews, observations, and documentation from eight business owners selected using purposive sampling. The results indicate that most MSMEs have not implemented structured financial planning and still rely on intuition when making business decisions. The lack of record keeping makes it difficult for business owners to identify operational costs, calculate profits accurately, and maintain cash flow stability. Meanwhile, MSMEs that separate business and personal finances and maintain regular financial records show better financial performance and development potential. This study concludes that improving financial literacy and applying disciplined financial management is essential in supporting the sustainability and growth of culinary MSMEs in Parepare. The findings are expected to contribute to strengthening managerial capacity and guiding stakeholders in empowering MSMEs through targeted financial management assistance